Simple lexicon - Språkbanken Text (University of Gothenburg, 2024)
The Swedish SIMPLE Lexicon - A language technology resource with access to semantic information in Swedish

Svenskt SIMPLE lexikon - En språkteknologisk resurs med semantisk information
Simple lexikon
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik